Effect of childhood obesity prevention programmes on blood lipids: a systematic review and meta‐analysis. Issue 12 (29th September 2014) - Cai, L.; Wu, Y.; Cheskin, L. J.; Wilson, R. F.; Wang, Y.
Summary We aimed to assess the effects of childhood obesity prevention programmes on blood lipids in high‐income countries. We searched MEDLINE®, Embase, PsychInfo, CINAHL®, clinicaltrials.gov, and the Cochrane Library up to 22 April 2013 for relevant randomized controlled trials, quasi‐experimental studies and natural experiments published in English. Studies were included if they implemented diet and/or physical activity intervention(s) with ≥1 year follow‐up (or ≥6 months for school‐based intervention studies) in 2–18‐year‐olds, and were excluded if they targeted only overweight/obese children, or those with a pre‐existing medical condition. Seventeen studies were finally included. For total cholesterol, the pooled intervention effect was −0.97 mg dL−1 [95% confidence interval (CI): −3.26, 1.32; P = 0.408]; for low‐density lipoprotein cholesterol (LDL‐C), −6.06 mg dL−1 (95% CI: −11.09, −1.02; P = 0.018); for high‐density lipoprotein cholesterol (HDL‐C), 1.87 mg dL−1 (95% CI: 0.39, 3.34; P = 0.013); and for triglycerides, −1.95 mg dL−1 (95% CI: −4.94, 1.04; P = 0.202). Most interventions (70%) showed similar significant or no effects on adiposity‐ and lipids outcomes: 15% interventions improved both adiposity‐ and lipids outcomes; 55% had no significant effects on either. Childhood obesity prevention programmes had a significant desirable effect on LDL‐C and HDL‐C. Two‐thirds of interventions showed similar significant or no effects in adiposity‐ and lipids outcomes. Assessing lipids outcomes provide additional useful information on obesity prevention programme benefits.